Systematic Literature Review on Sustainable Entrepreneurship in Circular Businesses - Teixeira, Marco Antonio Casadei; Bezerra , Claudia Maria da Silva; Ramos, Heidy Rodriguez (Scientific Journal ANAP, 2025)
Objective – The Circular Economy (CE) seeks to implement a production process that reuses resources and products, reducing energy consumption within an economic structure, aiming to enhance resource use efficiency and establish greater harmony and balance among the economy, the environment, and society.Methodology – This study conducted a Systematic Literature Review (SLR) of 56 studies on the topic, using Atlas.ti software to structure and analyze data collected from the Web of Science (WoS) and Scopus databases.Originality/relevance – The aim of the study was to map the academic literature on the adoption of CE practices in sustainable entrepreneurial business models.Results – The findings suggest that, for entrepreneurs to successfully transition to a CE, it is essential to study internal barriers, in contrast to external barriers, which are less explored in academic research. Both internal and external enablers are crucial for sustainable ventures and benefit from well-formulated policies and regulations.Theoretical/methodological contributions – It was found that barriers and enablers are important indicators for measuring the progress of entrepreneurial businesses toward a CE transition and provide professionals and researchers with insights to advance this shift.Social and environmental contributions – The results suggest that, for sustainable entrepreneurial businesses to succeed, stakeholders must learn to manage internal business barriers more effectively. The CE is crucial to enabling stakeholders toward sustainability, and studies on the drivers and obstacles of this transition are essential.
Keywords: Circular Economy; Sustainable Entrepreneurship; Sustainable Business Models.